A critical review on enhancing the seismic response of buildings with energy dissipation methods - Priya, D. Shanmuga; Cinitha, A.; Umesha, P.K.; Iyer, Nagesh. R. (Journal of Structural Engineering, 2025)
Buildings and other structures have mostly relied on their ability to dissipate energy during severe dynamic loading, such as wind and earthquake. In recent years as an outcome of research and development an innovative means to enhance structural functionality and safety against devastating earthquake and wind have been developed and integrated as a part of structures. Nowadays, the use of passive energy dissipaters, base isolators, active and hybrid control systems has increased to a tremendous extent. This paper reviews the existing technology that can be adopted to minimize the amount of damage and response of the structure under severe dynamic loads. Based on the review, it is observed that passive systems such as tuned mass dampers, friction dampers, tuned liquid dampers are used in structures located at moderate seismic zones and wind predominant regions. Base isolation is highly effective in protecting buildings from a devastating earthquake by considering proper initial design or by incorporating modifications to the buildings. Base isolators offer resistance to lateral movements induced by the ground. This provides flexibility to the connection between the structure and foundation and it is effective in low to medium rise buildings in hard soil. This paper highlights various forms of energy dissipation devices and structures integrated with energy dissipater’s performance during and after seismic events.